Pemeriksaan Trombosit dengan Teknik Homogenisasi Sekunder 4 kali, 8 kali dan Tanpa Homogenisasi Sekunder - Lidwina Septie Christyawardani Christyawardani; Margareta Haiti; Ummi Rizky Ramadani (Jurnal Kesehatan dan Pembangunan, 2022)
Platelet examination is often done in the laboratory to support the diagnosis of a disease. Platelet examination using a blood sample that has been mixed with EDTA anticoagulant. Homogenization technique is done by inversion by inverting the tube 8-10 times. However, when the sample has been taken and the primary homogenization of the blood sample has not been immediately carried out the examination because the sampling officer will still be around to take the blood of other patients so that when the blood arrives in the laboratory it must be homogenized again. This secondary homogenization, until now there is no provision and further research. This different secondary homogenization is the basis for researchers to conduct research to determine the results of the examination of platelets treated in a way without secondary homogenization, secondary homogenization was carried out 4 times and 8 times. It can be concluded that for the examination of platelets, it was found that there were differences in the blood samples which were subjected to primary homogenization, secondary homogenization with the inversion technique 4 times, 8 times and those which were not homogenized. However, this study has limitations in the study, namely not conducting research on homogenization techniques by means of number 8.